Women’s Life Trajectories in Rural Timor-Leste: A Life History and Life Course Perspective on Reproduction and Empowerment - Paola Borquez-Arce; Chiara E. Sumich; Raimundo da Costa; Gabriela Guizzo-Dri; Phoebe R. Spencer; Katherine Sanders; Debra S. Judge (Social Sciences)
Women’s reproductive decisions and life trajectories are shaped by an interplay of biological, social, and ecological factors. While Life History Theory (LHT) has traditionally been applied in biological sciences to examine reproductive trade-offs, its integration with Life Course Theory (LCT) and empowerment frameworks offers a novel approach to understanding how structural and environmental conditions shape women’s reproductive behaviours and household roles. This study applies Categorical Principal Component Analysis (CATPCA) to identify key profiles of women’s lives in two ecologically distinct rural communities in Timor-Leste—Ossu and Natarbora—and examines how these patterns relate to early life conditions. Building on a longitudinal study conducted in these communities, our findings reveal four distinct profiles: (1) Tech and Sanitation, linked to household labour-saving technology and higher education; (2) Traditional, reflecting large household size and livestock ownership; (3) Contraception, associated with fertility control, particularly among younger cohorts; and (4) High Fertility, characterised by more births, greater child mortality, and being born in high-altitude regions. By combining LHT, LCT, and the empowerment framework, this study analyses how reproductive strategies and household ecology intersect with structural inequalities. These findings offer key insights for policies aimed at improving women’s autonomy, access to resources, and reproductive health in rural Timor-Leste.